2014
DOI: 10.1016/j.ijhydene.2014.08.118
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation of two-phase pressure drop multiplier as a diagnostic tool for characterizing PEM fuel cell performance

Abstract: Temperature Cathode inlet RH Cell voltage Two-phase pressure drop Diagnostic tool a b s t r a c t Water management is a key area of interest in improving the performance of Proton Exchange Membrane fuel cells. Cell flooding and membrane dehydration are two extreme conditions arising from poor water management. Pressure drop has been recognized as a good diagnostic tool to determine the presence of liquid water in the reactant channels.Presence of liquid water in the channels increases the mass transport resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 46 publications
(42 reference statements)
1
14
0
1
Order By: Relevance
“…We note that the two-phase multiplier decreases with increase in current density. This has been observed in previous studies, 6,24,35,50,51 and has been attributed to the increase in air velocity with increasing current density, which results in the change in flow patterns with increasing gas velocities. The phenomenon is observed because with increasing current density, there is an increase in both the gas flow rate (due to increased reactant consumption and a constant stoichiometric ratio being maintained) and the water flow rate (increased water generation).…”
Section: Validation Studiessupporting
confidence: 75%
See 1 more Smart Citation
“…We note that the two-phase multiplier decreases with increase in current density. This has been observed in previous studies, 6,24,35,50,51 and has been attributed to the increase in air velocity with increasing current density, which results in the change in flow patterns with increasing gas velocities. The phenomenon is observed because with increasing current density, there is an increase in both the gas flow rate (due to increased reactant consumption and a constant stoichiometric ratio being maintained) and the water flow rate (increased water generation).…”
Section: Validation Studiessupporting
confidence: 75%
“…6 This is due to the change in flow patterns which have a direct effect on the resistance offered to the gas flow through the channel. Therefore, it is important to use the separated flow model (Lockhart and Martinelli approach shown in Eqs.…”
Section: Validation Studiesmentioning
confidence: 99%
“…At an operating current density of 1.5 A • cm −2 , Chevalier et al [66] observed an increase in peak local liquid water saturation from <5% to 86% when the cathode RH was varied from 25% to 100%. In addition to the direct studies of GDL water mentioned above, numerous studies have studied PEM fuel cell liquid water accumulation in the channels via direct visualization or measurement of pressure drop [26][27][28][67][68][69][70][71][72][73]. In the studies by Banerjee et al [67], Hussaini and Wang [68] and Spernjak et al [27], increases in the inlet reactant gas RH were observed to increase the presence of liquid water in the channels.…”
Section: Effect Of Reactant Gas Relative Humidity (Rh)mentioning
confidence: 99%
“…The addition of the hydrophilic layer led to enhanced membrane hydration and fuel cell performance (see also power density curves) under low humidity conditions. However, the GDL with hydrophilic coating 2 exhibited higher mass transport resistance at 2 A/cm 2 and reached a limiting current before reaching the 2.5 A/cm 2 current step. Fig.…”
Section: Effect Of Hydrophilic Coating On Membrane Resistancementioning
confidence: 95%
“…Water management in the PEM fuel cell is critical for balancing two competing needs: a) adequate hydration of the polymer electrolyte membrane for protonic conductivity, and b) preservation of oxygen mass transport pathways for fuel delivery by reducing excess water accumulation at the cathode GDL [2]. To hydrate the membrane and prevent "membrane dry-out", external humidifiers are conventionally incorporated into the fuel cell system.…”
Section: Introductionmentioning
confidence: 99%